2016
DOI: 10.1177/0960327115622258
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of Prussian blue nanoparticles after short exposure of mice

Abstract: Prussian blue nanoparticle (PBNP), a new type of theranostic nanomaterial, had been used for cancer magnetic resonance imaging and photothermal therapy. However, their long-term toxicity after short exposure in vivo was still unclear. In this study, we investigated the dynamic changes of the biochemical and immunity indicators of mice after PBNPs injection through tail vein. Histological results showed that the PBNPs were mainly accumulated in liver and spleen. In the spleen, we found the frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…These include hollow gold nanoshells, 34 CpG-loaded MoS 2 nanosheets, 35 graphene oxide, 36 Al2O3 nanoparticles, 37 and hollow CuS nanoparticles 5 . Compared with earlier studies, our work is distinct for the following reasons: 1) Prussian blue is a United States FDA-approved material as Radiogardase® and listed as an essential medicine by the World Health Organization as a radioactive poisoning antidote, 38 which indicates the safety of working with PBNPs, 2) PBNPs are biodegradable, 9 which mitigates concerns associated with the long-term fate and associated toxicities of nanoparticles within the body, 39 3) we describe a facile method for coating CpG onto the PBNPs that enables the simultaneous delivery of tumor cell death, antigenicity, and adjuvanticity in a single nanoparticle, and 4) PBNPs combined with toll-like receptor agonists have not previously been applied to treat neuroblastoma.…”
Section: Introductionmentioning
confidence: 96%
“…These include hollow gold nanoshells, 34 CpG-loaded MoS 2 nanosheets, 35 graphene oxide, 36 Al2O3 nanoparticles, 37 and hollow CuS nanoparticles 5 . Compared with earlier studies, our work is distinct for the following reasons: 1) Prussian blue is a United States FDA-approved material as Radiogardase® and listed as an essential medicine by the World Health Organization as a radioactive poisoning antidote, 38 which indicates the safety of working with PBNPs, 2) PBNPs are biodegradable, 9 which mitigates concerns associated with the long-term fate and associated toxicities of nanoparticles within the body, 39 3) we describe a facile method for coating CpG onto the PBNPs that enables the simultaneous delivery of tumor cell death, antigenicity, and adjuvanticity in a single nanoparticle, and 4) PBNPs combined with toll-like receptor agonists have not previously been applied to treat neuroblastoma.…”
Section: Introductionmentioning
confidence: 96%
“…It can also control the H 2 O 2 decomposition rate via local temperature variation of PBNPs under NIR laser irradiation [50]. More importantly, several reports demonstrated that PBNPs have good biocompatibility and nontoxicity because of the tight bond between the cyano groups and iron [51,52]. Therefore, PBNPs-based composites might serve as a promising theranostics nanoplatform and overcome limitations such as a lack of accuracy, sensitivity, and real-time diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Prussian blue nanoparticles were previously described as biosensors, based on their redox properties. Their peroxidase-like activity was in focus of the studies of Zhang et al and Vázquez-González et al Their studies suggest that the interaction of cells with PBPNs could enhance the effects of oxidative damage to cells, especially to the cells of the liver, which was observed in the work of Chen et al [ 33 , 34 , 35 ]. To overcome the oxidative effects of PBNP administration, either reductive substance should be administered with the PBNPs or reductase-like activity should be attached to the surface of the PBNPs.…”
Section: Discussionmentioning
confidence: 99%
“…They found that, however, PBNPs induced acute damage in the liver (based on the liver functions), the long-term effects of PBNP-treatment cannot be called negative. All monitored parameters returned to normal levels, 60 days after the first IV PBNP administration [ 35 ]. Our results also confirm the claims of Chen et al; in the ex vivo images ( Figure 4 ), PBNPs were present in the spleen and the liver; biliary functions resulted in PBNP presence in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%